Marvel's the Avengers [videorecording (Blu-Ray)] - Whedon, Joss, 1964-; Downey, Robert, Jr., 1965-; Johansson, Scarlett, 1984-; Renner, Jeremy; Ruffalo, Mark; Hemsworth, Chris; Hiddleston, Tom; Paltrow, Gwyneth, 1972-; Jackson, Samuel L.; Skarsgård, Stellan; Bettany, Paul, 1971-; Lee, Stan, 1922-2018; et al. (Marvel : Distributed by Buena Vista Home Entertainment, 2012)
Marvel makes cinematic history as it unites the superhero team-up of a lifetime. Iron Man, the Hulk, Thor, and Captain America assemble together for the very first time ever in this epic, action-packed blockbuster alongside Black Widow, Hawkeye, and Nick Fury.